A Masquerading Case of IGRA Positive Mycobacterium Szulgai - Grace Salame; Mohammed Abdulkadir Alhassen; Manjunath Muddaraju; Nirav Patel; Sowmya Nanjappa (Global Journal of Rare Diseases - Peertechz Publications, 2017)
It is well known that Interferon-gamma release assays (IGRAs) are more specific than the purified protein derivative (PPD) skin tests in diagnosing tuberculosis as it is not confounded by prior bacillus Calmette-Guérin (BCG) vaccination. We present a unique case of false positive IGRA in a 57 year old female with Mycobacterium szulgai cavitary lung infection.